2003
DOI: 10.1093/ps/82.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mucosal immunity against Eimeria acervulina in broilers fed a Lactobacillus-based probiotic

Abstract: The effect of feeding a Lactobacillus-based probiotic on intestinal intraepithelial lymphocyte (IEL) subpopulations and subsequent protection against coccidiosis was investigated in broiler chickens. Day-old male broilers were fed standard rations without control (CONT) or with a commercial probiotic (PROB) Primalac. Differences in IEL subpopulations were assessed by flow cytometry at 21 d postprobiotic treatment. At 25 d of age, a group of randomly selected birds from each diet was inoculated orally with 10,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
137
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(148 citation statements)
references
References 21 publications
8
137
1
2
Order By: Relevance
“…Today, addition of probiotic in diet is a common strategy for animal nutrition, because probiotic is a natural growth promoter instead of feed antibiotic (Rekiel et al 2007). Adding probiotic in the diet improves the animal immune system and the host's resistance to enteric pathogens, affects intestinal morphology as well as intestinal function, feed conversion, weight gain and performance of birds (Dalloul et al 2003, Chichlowski et al 2007, Vila et al 2009, Ohh 2011. Li et al (2006) also reported that addition of Bacillus subtilis culture to the layer diet decreased cholesterol concentration in egg yolk.…”
Section: Introductionmentioning
confidence: 99%
“…Today, addition of probiotic in diet is a common strategy for animal nutrition, because probiotic is a natural growth promoter instead of feed antibiotic (Rekiel et al 2007). Adding probiotic in the diet improves the animal immune system and the host's resistance to enteric pathogens, affects intestinal morphology as well as intestinal function, feed conversion, weight gain and performance of birds (Dalloul et al 2003, Chichlowski et al 2007, Vila et al 2009, Ohh 2011. Li et al (2006) also reported that addition of Bacillus subtilis culture to the layer diet decreased cholesterol concentration in egg yolk.…”
Section: Introductionmentioning
confidence: 99%
“…(Pascual et al, 1999), Campylobacter sp. (Stern et al, 2001) and, more recently, Eimeria acervulina (Dalloul et al, 2003). Proposed mechanisms of pathogen inhibition by the probiotic microorganisms include competition for nutrients, production of antimicrobial conditions and compounds (volatile fatty acids, low pH, and bacteriocins), competition for binding sites on the intestinal epithelium, and stimulation of the immune system (Rolfe, 2000).…”
mentioning
confidence: 99%
“…The output of oocysts in the faeces is a widely used method in disease diagnosis and also a measure for the infection severity (Chapman and Rayavarapu, 2007). Furthermore, it says something about the chickens' resistance to Eimeria (Dalloul et al, 2003), the higher the oocyst production, the lower the resistance to Eimeria. These observations all indicate that SI chickens had a lower capacity to adapt during the E. acervulina infection than OI chickens.…”
Section: Discussionmentioning
confidence: 99%